2006
DOI: 10.1590/s1517-83822006000300022
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin glycosyltransferase from Bacillus licheniformis: optimization of production and its properties

Abstract: Cyclodextrin glycosyltransferase (EC 2.4.1.19) is an enzyme that produces cyclodextrins from starch via an intramolecular transglycosylation reaction. An alkalophilic Bacillus strain, isolated from cassava peels, was identified as Bacillus licheniformis. CGTase production by this strain was better when potato starch was used as carbon source, followed by cassava starch and amylopectin. Glucose and amylose, on the other hand, acted as synthesis repressors. When the cultivation was supplemented with sodium ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Moreover, some Brazilian researchers have reported the isolation and production of CGTases by Bacillus sp. (2,3,9,15,16,17,19,21). This work reports the isolation of new Bacillus sp.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, some Brazilian researchers have reported the isolation and production of CGTases by Bacillus sp. (2,3,9,15,16,17,19,21). This work reports the isolation of new Bacillus sp.…”
Section: Introductionmentioning
confidence: 93%
“…However, the greatest CGTase specific activity for the three isolated strains was obtained when growth occurred at 40ºC. Bonilha et al (3) reported that the greatest activity of BACNC-2 was obtained when culture occurred at 37ºC. Martins and Hatti-Kaul (21) showed that B. agaradherens LS-3C produced CGTase when cultivated at 37ºC and Larsen et al (12) showed that the CGTase production by Paenibacillus also occurred at 37ºC.…”
Section: Determination Of the Optimum Temperature For Cgtase Enzyme Pmentioning
confidence: 99%
“…2013;11 (4) For minimization of the learning error during the neural network training it is necessary to iteratively update the network weights. Different learning algorithms…”
Section: Artificial Neural Network Analysis Of β-Cd Productionmentioning
confidence: 99%
“…They are produced during degradation of starch by cyclodextrin glucanotransferases (CGTase) (EC 2.4.1.19) which is commercially available or can be produced by some microorganisms especially diverse strains of Bacillus such as Bacillus circulans (1). Bacillus macerans, Bacillus firmus (2) and Bacillus licheniformis (3)(4)(5). The capability of cyclodextrins (CDs) to form inclusion complexes and modify the physical and chemical properties of the guest molecules, makes them extremely attractive for vast industrial applications such as food, chemical, pharmaceutical, and textile, as well as in biotechnology and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…They are the 6 glucose CDs (or a -CD), the 7 glucose CDs (or b -CD) and the 8 glucose CDs (or g -CD). CGTases are present in microorganisms including Bacillus , Klebsiella , Micrococcus, and Clostridium (Bonilha et al 2006 ;Menocci et al 2008 ) .…”
Section: Transferasesmentioning
confidence: 99%